Bioactive compound combinations from Rhodiola tangutica alleviate pulmonary vascular remodeling in high-altitude pulmonary hypertension rats through the PI3K–AKT pathway - Yang, Na; Huayu, Meiduo; Su, Shanshan; Hou, Bin; Yang, Zhanting; Nan, Xingmei; Li, Zhanqiang (Frontiers in Pharmacology, 2025)
BackgroundHypoxia-induced pulmonary vascular remodeling is central to the development of high-altitude pulmonary hypertension (HAPH). Rhodiola tangutica has traditionally been used to prevent chronic mountain sickness. Although its active fraction (ACRT) shows therapeutic potential for HAPH, the main pharmacodynamic substances remain unclear due to its complex composition.AimsThis study aimed to identify bioactive equivalent combinatorial components (BECCs) of ACRT that alleviate pulmonary vascular remodeling in HAPH rats and explore the underlying pharmacological mechanisms.MethodsSeventy adult Sprague–Dawley rats were divided into control, hypoxia, hypoxia + ACRT (150 mg/kg), hypoxia + BECCs (25, 50, and 100 mg/kg), and hypoxia + sildenafil (30 mg/kg) groups. An HAPH rat model was induced using a hypobaric hypoxia chamber simulating an altitude of 5,000 m. The effects of BECCs on pulmonary vascular remodeling in HAPH rats were evaluated based on hemodynamic indexes and histopathological changes, alongside antioxidant properties. Phosphoproteomics and Western blotting were performed to analyze AKT1-related protein expression in lung tissues. In vitro, 3% O2-induced pulmonary artery smooth muscle cell (PASMC) models were used to evaluate the anti-proliferative effects of BECCs and identify the dominant components. The underlying mechanisms were explored using Western blotting and a drug affinity responsive target stability (DARTS) assay to assess binding affinity.ResultsHAPH rat models were successfully established, as evidenced by changes in physiological parameters. BECCs showed comparable efficacy to ACRT in restoring hemodynamic indexes and histopathological changes. Mechanistically, BECCs modulated AKT phosphorylation and related protein expression. In vitro, BECCs inhibited hypoxia-induced PASMC proliferation. Particularly, flavonoids (FLAs) within BECCs exhibited stronger anti-proliferative activity than other components, acting as the dominant contributors by regulating phosphatidylinositol-3 kinase (PI3K) rather than phosphoinositide-dependent protein kinase (PDPK) or mammalian target of rapamycin (mTOR) pathways to inhibit AKT phosphorylation. Among FLAs, eriodictyol and quercetin were found to inhibit PASMC proliferation by targeting PI3K.ConclusionBECCs demonstrated comparable efficacy to ACRT in alleviating HAPH progression, reversing hypoxia-induced vascular remodeling, and inhibiting oxidative stress and PASMC proliferation by targeting the AKT protein. Flavonoids were identified as the key bioactive components contributing to the holistic effects of BECCs by regulating phosphatidylinositol-3 kinase/protein kinase B (PI3K/AKT) pathways. These findings could be extended to improve quality control and clarify the bioactive components of R. tangutica while inspiring development of combinatorial therapies for HAPH treatment.